Unilateral pulmonary veins atresia: evaluation by computed tomography - Eifer,Diego André (2013)
Unilateral pulmonary vein atresia is a rare congenital condition. In addition to cardiac malformations or pulmonary hypertension, patients may present with recurrent pulmonary infections or hemoptysis in childhood or adolescence. The authors report a case where the typical findings of such condition were observed at computed tomography in an adult patient.